Overexpression of bone morphogenetic protein 2 through aberrant canonical Wnt/β-catenin signaling pathway plays an important role in heterotopic ossification of adrenal myelolipoma - Mitsui, Yozo; Yasumoto, Hiroaki; Hiraki, Miho; Arichi, Naoko; Ishikawa, Noriyoshi; Harada, Yuji; Maruyama, Riruke; Shiina, Hiroaki (Canadian Urological Association Journal, 2014)
The precise mechanism of heterotopic ossification caused by several types of tumours is largely unknown. However, recent studies have indicated that bone morphogenetic protein 2 (BMP2) is closely linked to the Wnt/β-catenin signaling pathway in this rare phenomenon of bone formation. We report a rare case of adrenal myelolipoma (ML) in a 27-year-old woman with heterotopic bone formation. Immunohistochemical findings showed BMP2 expression in the cytoplasm of tumour cells, as well as the matrix adjacent to newly developed bone tissue. In addition, β-catenin was prominent in the cytoplasm and nuclei of BMP2-positive tumour cells. To the best of our knowledge, this is the first report of adrenal ML showing heterotopic ossification with accelerated expression of both BMP2 and β-catenin. Our case findings indicate that BMP2 overexpression via aberrant canonical Wnt/β-catenin signaling may contribute to heterotopic bone formation occurring in adrenal ML.